Handbook of research on network forensics and analysis techniques - Shrivastava, Gulshan 1987 (2018)
"This book explores the latest advances in network forensics and analysis techniques. It explores topics such as network security: attacks and controls, analysis of attacks, defenses, and countermeasures, anonymity, privacy, id theft and ethics, dependability and security forensics, denial-of-service, and botnet analysis, detection, and mitigation"--